‘Burning Questions’: The Role of Conversation and Student-Led Research Topics in Developing Intellectual Curiosity. - Hardenberg, Wendeline A (Intellectual Curiosity and the Role of Libraries: The First and Second Year College Student Experience, 2023)
Keywords: dept.lob

City Mazes Around the World Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
From New York City to Tokyo and Berlin to Sydney, the streets of the 15 cities included in this book are filled with a fascinating showcase of local landmarks and awesome attractions. How will you get from the Brooklyn Bridge to Central Park in New York City? Or find your way to Topkapi Palace in Istanbul? Each spread
Keywords: dept.lib

Mr. Bear's Birthday Translated by Wendeline Hardenberg - Aracil, Virginie (Twirl Books, 2020)
Mr. Bear is having a birthday party, and everyone is welcome! It doesn’t matter if you’re big, small, don’t have teeth, or are afraid of the dark . . . you’re invited! In this wonderfully illustrated oversize book that celebrates inclusion as well as a special day, Mr. Bear’s Birthday also includes lots of gifts—with f
Keywords: dept.lib

Who Does What? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Who gathers honey? Who designs clothes? Who makes lunch for students?  So many jobs can be found in this delightful and satisfying sliding panel format for preschoolers. The 36 panels feature jobs in various settings: in the orchestra, at the market, at school, and more! Each new spread offers clues to the right respon
Keywords: dept.lib

The Ultimate Book of Horses Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl Books, 2020)
Horses are amazing creatures! The Ultimate Book of Horses provides hours of hands-on discovery and includes age-appropriate information on the …
Keywords: dept.lib

Miki Takes a Bath Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Splish-splash! Miki’s taking a bath! Bathtime couldn’t be more fun with Miki showing how it’s done in this delightful pop-up …
Keywords: dept.lib

Animals at Night Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl Books, 2020)
The fluffy feathers of an owl, the bumpy skin of a toad, and the thick fur of a river otter—there’s …
Keywords: dept.lib

Trains Translated by Wendeline Hardenberg - Prénat, Sophie (Twirl Books, 2020)
All aboard! Chock-full of fascinating facts, Ultimate SpotlightTM Trains offers young readers a closer look into the marvelous world of …
Keywords: dept.lib

Mr. Lion Dresses Up! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl Books, 2020)
How exciting! Mr. Lion has been invited to a party! But what will he wear? A handsome suit . . …
Keywords: dept.lib

Whose Baby is This? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Keywords: dept.lib

“The Master of Scents” * Fiction * By Vincent Ravalec * Translated by Wendeline A. Hardenberg - Ravalec, Vincent (Aromatica Poetica, 2022)
He was the Master of Scents. He ruled over them, classified them, harnessed them, recombined them, invented them, and above all took care of their dis...
Keywords: dept.lib

From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg - Aubry, Gwenaëlle (Columbia Journal, 2021)
From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg
Keywords: dept.lib

The Bookshop of Forgotten Dreams: A page-turning opposites attract romantic comedy! Translated By Wendeline Hardenberg - Blaine, Emily (One More Chapter, 2021)
Keywords: dept.lib

Crack-Crack! Who Is That? Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2022)
Keywords: dept.lib

This Book Can Do Anything Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2021)
Keywords: dept.lib

Mr. Lion's New Hair! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Oceans and Marine Life Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Dinosaurs and the Prehistoric World Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl, 2021)
Keywords: dept.lib

Little Bug on the Move Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

SURPRISE! Slide and Play Shapes Translated by Wendeline Hardenberg - Fouquier, Elsa (Twirl, 2021)
Keywords: dept.lib

Patience Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Waiting is not easy, whether it’s waiting to play with a toy or to eat a snack. And Little Kangaroo, Little Cat, and their friends are just not sure that they can be patient. But as their grown-ups show them, being patient doesn’t have to be boring or unbearable. There are many fun things they can do while they wait! C
Keywords: dept.lib

Magnetology: Vehicles Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2020)
Take a ride—whether it’s on a boat, plane, or on a rocket ship! Kids can use the 45 magnetic pieces included to fill 5 oversized scenes in this Magnetology™ title. The all-in-one play set features fascinating information, just right for its audience, about all types of vehicles: those that travel on the road, on a farm
Keywords: dept.lib

Brothers and Sisters Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends have siblings—siblings who take their things, make a mess, or just get …
Keywords: dept.lib

Ultimate Spotlight: Polar Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

With Death, an Orange Segment Between Our Teeth, poems by Marie-Claire Bancquart - Bancquart, Marie-Claire (Orison Books, 2023)
With Death, an Orange Segment Between Our TeethMarie-Claire BancquartTranslated from the French by Wendeline A. Hardenberg *Available for pre-order.* Orison Bookspaper / 178 pp. / $18.00bilingualISBN: 978-1-949039-42-9Distributed to the trade by Itasca Books952-223-8373 / orders@itascabooks.comPublication Date: November 7, 2023 ABOUT THE BOOK Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic. In her poetry, she combines an erudite vocabulary and references to classical literature with an earthy sensibility and a fascination with experiencing the smallest moments of everyday life fully. The deceptive simplicity of her poems lays bare the mysteries underlying the world we inhabit and our very existence. Wendeline A. Hardenberg’s careful and skillful translations are sure to broaden the audience for this significant poet as yet too little known outside of France. PRAISE Deeply philosophical, these poems, originally published in French when the author was in her seventies, focus on the meaning of existence. The poet reminds us that our lives—“seven liters of water wrapped in skin”—are “small,” but “the universe [is] in us / us in the universe.” From our “ephemeral perch on the earth,” writing achieves a kind of immortality, producing “a few words warmed by the journey, / that scatter outside, vouching / that you gave them a little extra life.” Readers will be grateful to Hardenberg for carefully shepherding these provocative poems into English. —Nancy Naomi Carlson, recipient of The Oxford-Weidenfeld Translation Prize Strange and wonderful translations of strange and wonderful poems... Marie-Claire Bancquart’s voice is utterly unique; her poems—by turns lyrical and jarring, mystical and forthright, tender and brutal—sing and clamor in your head long after you’ve read them. Like their French originals, Hardenberg’s excellent translations glitter and dart and unsettle; they dodge like wrestlers, then they grab you by the throat and won’t let go. This is rich writing to come back to again and again; each time you’re ambushed by some startling image or phrase or notion that you hadn’t noticed before. A vital book, both in the sense of its aliveness and its urgency.—Bill Johnston, recipient of The PEN Translation Prize ABOUT THE AUTHOR & TRANSLATOR Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic, as well as a Professor Emerita of French literature at the Sorbonne. Her final book, De l'improbable, précédé de Mo(r)t, was published by Éditions Arfuyen in 2020. Wendeline A. Hardenberg studied at Smith College and Indiana University, where she earned master’s degrees in Comparative Literature with a focus on translation and Library Science. She is the translator of numerous books, including The Bookshop of Forgotten Dreams by Emily Blaine, Will You Ever Change? by Aurélie Valognes, and Project Anastasis by Jacques Vandroux. Hardenberg’s translations have been published in Asymptote, Columbia Journal, Metamorphoses, Tupelo Quarterly, Two Lines, and other places. She lives in New Haven, Connecticut. SAMPLE POEM Close The blackberriesare clotted profusely in the bushes we are so close to the secret of this worldthat it seems to be awaitingjusta small steplike onto a balcony, to smell a flower. We don’t move that would be to wound the beingalmost managing to bein view of the fruits’ black boiling.
Keywords: dept.lib; literary-poetry

The Pop-Up Guide: Natural Wonders Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

What About: Science Translated by Wendeline Hardenberg - Fichou, Bertrand (Twirl, 2022)
Keywords: dept.lib

Ultimate Spotlight: Volcanoes Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Space and Sky Translated by Wendeline Hardenberg - Hardenberg, Wendeline A. (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Vehicles Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

Magnetology: Animals Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

Matching Game Book: Bugs and Other Little Critters Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Space Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Rain Forest Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

Animal Friends 1 2 3 Translated by Wendeline Hardenberg - Loupy, Christopher (Twirl, 2021)
Keywords: dept.lib

Miki Gets Dressed Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl, 2021)
Keywords: dept.lib

The Ultimate Book of Water Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl, 2022)
Keywords: dept.lib

Pull and Play Books: Let's Be Safe Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Pull and Play: Pacifier Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Sharing: A Pull-the-Tab Book Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Vehicles and Transportation Translation by Wendeline Hardenberg - Hardenberg, Wendeline A. (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Animals of Land, Sea, and Air Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Earth and Nature Translated by Wendeline Hardenberg - Benoist, Cécile (Twirl, 2022)
Keywords: dept.lib